2020
DOI: 10.1111/bcp.14488
|View full text |Cite
|
Sign up to set email alerts
|

Use of proton pump inhibitors is associated with lower rates of first‐time ischemic stroke in community‐dwelling elderly

Abstract: Aim Data on cardiovascular outcomes in elderly using proton pump inhibitors (PPI) are scant. We aimed to test the association between PPI use and the occurrence of first‐time ischemic stroke (FTIS) among elderly. Methods The electronic database of a centrally located district branch of a large health maintenance organization in Israel was retrospectively screened (2002–2016) for community‐dwelling individuals (≥65–95 years) for demographics and co‐morbidities. Follow‐up was until FTIS, death or end of study. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Several studies have shown an association between chronic use of PPIs and serious adverse effects, including Clostridium difficile and other enteric infections, intestinal colonization with multidrug-resistant microorganisms, hospital and community-acquired pneumonia, dementia, osteoporotic fractures, hypomagnesemia, and acute interstitial nephritis (4,8,10,11) . Recent retrospective observational studies suggest a likely association between long-term, high-dose PPIs use and a low increased risk of first-time ischemic stroke, especially in elderly patients (12,13) . In terms of economic burden, GASs prescription leads to a progressive increase of public health costs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an association between chronic use of PPIs and serious adverse effects, including Clostridium difficile and other enteric infections, intestinal colonization with multidrug-resistant microorganisms, hospital and community-acquired pneumonia, dementia, osteoporotic fractures, hypomagnesemia, and acute interstitial nephritis (4,8,10,11) . Recent retrospective observational studies suggest a likely association between long-term, high-dose PPIs use and a low increased risk of first-time ischemic stroke, especially in elderly patients (12,13) . In terms of economic burden, GASs prescription leads to a progressive increase of public health costs.…”
Section: Introductionmentioning
confidence: 99%
“…In a population‐based cohort study, Schmilovitz‐Weiss et al 14 (BJCP 2020) evaluated 29 639 patients (with no history of stroke and/or use of antiplatelet aggregation drugs) with a mean age of 82.2 ± 5.5 years who were using PPIs. They discovered that the risk for a first‐time ischemic stroke was significantly lower in those using PPIs at any dose and for any time period compared to non‐users.…”
Section: System/organ Adverse Effect Key Findings Studymentioning
confidence: 99%
“…In their view, considering the low incidence of clinically important upper GIB in the ICU patients, prophylaxis with a PPI, if started, should be reserved only for severely ill patients with an increased risk for this complication (Figure 1). In a population-based cohort study, Schmilovitz-Weiss et al 14 (BJCP 2020) evaluated 29 639 patients (with no history of stroke and/or use of antiplatelet aggregation drugs) with a mean age of 82.2 ± 5.5 years who were using PPIs. They discovered that the risk for a first-time ischemic stroke was significantly lower in those using PPIs at any dose and for any time period compared to non-users.…”
mentioning
confidence: 99%